Extending the Conceptual Base for a Holistic Quality Evaluation Approach - Rivera, Belén (2015)
For software organizations often performing measurement, evaluation (ME), and even change/improvement (MEC) projects, a wellestablished quality evaluation approach can be useful. In this direction, we have developed a holistic quality evaluation approach whose architecture is based on two pillars, namely: a quality multi-view modeling framework, and ME/MEC integrated strategies. In this paper, we specify the conceptual base for the former pillar. Specifically, we specify an ontology of quality views documenting its main terms, properties and relationships. Quality views are paramount for selecting evaluation strategies and strategy patterns to be assigned as resources to ME/MEC projects. Also, we show how this ontology is semantically linked with the previously built ME domain ontology.